Direct aspiration first pass technique for the treatment of acute ischemic stroke: initial experience at a European stroke center. (12th January 2015) - Kowoll, Annika; Weber, Anushe; Mpotsaris, Anastasios; Behme, Daniel; Weber, Werner
Abstract : Introduction: Over the past decade, endovascular techniques for the treatment of acute ischemic stroke have emerged significantly. However, revascularization rates are limited at approximately 80%, and mechanical thrombectomy procedures still last about 1 h. Therefore, we investigated the novel direct aspiration first pass technique for its efficacy and safety. Methods: Our neurointerventional database was screened for patients who received mechanical thrombectomy for acute ischemic stroke using the Penumbra 5MAX ACE aspiration catheter on an intention to treat basis between November 2013 and June 2014. Procedural data, including modified Thrombolysis in Cerebral Infarction (mTICI) score, procedural timings, and complications, as well as clinical data at admission and discharge, were analyzed. Results: 54 patients received mechanical thrombectomy using the 5MAX ACE. Median age was 69 (39–94) years (54% were men). Baseline National Institutes of Health Stroke Scale (NIHSS) score was 15 (2–27) and 44/54 (81%) patients received intravenous thrombolysis. Vessel occlusion sites were 91% anterior circulation and 9% posterior circulation. A successful revascularization result (mTICI ≥2b) was achieved in 93% of cases whereas direct aspiration alone was successful in 30/54 (56%) cases; among these, median time from groin puncture to revascularization was 30 min (9–113). Symptomatic intracranial hemorrhage occurred in 2/54 (4%) patients, and embolization to new territories in 3/54 (6%). Median NIHSS at discharge was 6 (0–24); 46% of patients were independent at discharge. Conclusions: The direct aspiration first pass technique proofed to be fast, effective, and safe. Promising revascularization results can be achieved quickly in more than 50% of patients using this technique as the firstline option. Nevertheless, stent retrievers are still warranted in approximately 40% of cases to achieve a favorable revascularization result.